2006
DOI: 10.1021/jf062461v
|View full text |Cite
|
Sign up to set email alerts
|

Residues and Persistence of Neem Formulations on Strawberry after Field Treatment

Abstract: Azadirachtoids were determined by liquid chromatography/mass spectrometry (LC/MS) in five methanolic seed extracts of the neem tree and in a commercial formulation. On average, seed extracts contain azadirachtin A (10.9%), azadirachtin B (3.5%), nimbin (10.4%), and large quantities of salannin (19.0%). The composition of the commercial formulations may present different azadirachtoids contents depending on the natural extracts used in the preparation. Because these compounds may also show insecticide activity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 10 publications
2
44
0
9
Order By: Relevance
“…This occurs because azadirachtin and related compounds undergo very rapid degradation. Caboni et al (2006) extracted some limonoids from methanolic extracts of neem seeds and exposed them to sunlight; the halflives calculated for azadirachtin, 3-tigloylazadirachtol, nimbin and salanin were 11.34, 5.52, 0.30 and 0.09 hours, respectively. Our bioassays showed that the effect of neem was neither maintained nor increased over time with nanoformulations.…”
Section: Treatmentmentioning
confidence: 99%
“…This occurs because azadirachtin and related compounds undergo very rapid degradation. Caboni et al (2006) extracted some limonoids from methanolic extracts of neem seeds and exposed them to sunlight; the halflives calculated for azadirachtin, 3-tigloylazadirachtol, nimbin and salanin were 11.34, 5.52, 0.30 and 0.09 hours, respectively. Our bioassays showed that the effect of neem was neither maintained nor increased over time with nanoformulations.…”
Section: Treatmentmentioning
confidence: 99%
“…In addition, the action of neem products decreases with time, which is attributed to environmental factors mainly temperature, sunlight UV radiation and rain (CABONI et al, 2006;BERNARDI et al, 2012;SCHLESENER et al, 2012). The short residual action of the product should be compensated with reapplication at 7 days intervals (CABONI et al, 2006;BERNARDI et al, 2012), which was also observed for the yerba mate crop.…”
Section: Resultsmentioning
confidence: 99%
“…Entretanto, EFEITOS DO NIM SOBRE Tetranychus urticae KOCH (ACARI: TETRANYCHIDAE)... existem outras substâncias presentes no óleo de nim que causam efeitos importantes para a regulação da população, como é o caso dos terpenos nimbina e salanina. Esses dois compostos também são responsáveis pela diminuição na fecundidade, repelência e esterilidade dos ovos (CARBONI et al, 2006). Persistência biológica sobre T. urticae Nas avaliações de 0; 24 e 48h, com transferências de T. urticae em 0; 24 e 48 HAP, foram verificadas diferenças significativas do produto Azamax ® (0,5 e 1,0%) em relação à testemunha.…”
Section: Persistência Biológicaunclassified
“…De acordo com Carboni et al (2006), essa rápida degradação pode ser consequência da fotodegradação e da temperatura. As azadiractinas A e B, expostas ao sol, degradam em aproximadamente 11,34 e 5,52 h, respectivamente.…”
Section: Persistência Biológicaunclassified
See 1 more Smart Citation